CLIENT-CENTERED OCCUPATIONAL THERAPY APPROACHES IN RESTORING FUNCTIONAL INDEPENDENCE OF MILITARY PERSONNEL WITH COMBAT-RELATED INJURIES (Physical Culture and Sport: Scientific Perspective, 2025)
The full-scale war in Ukraine has underscored the critical need for effective rehabilitation strategies tailored to military personnel with complex combat-related injuries. Conventional biomedical rehabilitation models, which often prioritize the restoration of physical functions, fall short in addressing the multifaceted needs of these individuals, whose injuries frequently combine physical trauma with significant psycho-emotional challenges, such as post-traumatic stress disorder and depression. This necessitates a shift towards a more holistic, client-centered approach that views the service member as an active partner in their recovery, not a passive recipient of care. This methodology, widely supported by international best practices, focuses on restoring meaningful life occupations, roles, and activities as the primary goal of therapy.The purpose of this article is to provide a theoretical substantiation and practical analysis of client-centered approaches in occupational therapy aimed at restoring the functional independence of military personnel with combat trauma. The study highlights the pivotal role of occupation-based interventions as a core principle of the rehabilitation process and advocates for the integration of the biopsychosocial model into contemporary occupational therapy practice. A key focus is to identify the most effective assessment tools for objectively measuring functional status and integrating the patient's subjective priorities, which is a major unresolved issue in the domestic context.Through a comprehensive literature review and an analysis of international experience from countries such as the United States, Canada, and the United Kingdom, the study confirms that multidisciplinary and client-centered assessment tools are crucial for successful rehabilitation. Tools like the Canadian Occupational Performance Measure (COPM) are found to be highly effective in identifying patient-prioritized goals. A survey of occupational therapists in Ukraine, however, reveals that while there is awareness of such tools, the most commonly used instruments remain the Barthel Index and Functional Independence Measure (FIM), which are simpler but less sensitive to individual goals and holistic outcomes. The findings indicate a critical need for the systematic adoption and cultural adaptation of modern client-centered assessment instruments within the Ukrainian rehabilitation system.The article concludes that for Ukrainian occupational therapy to meet the complex needs of military personnel with combat trauma, it must embrace a client-centered philosophy, prioritize occupation-based interventions, and integrate validated assessment tools that support a biopsychosocial model of care. This will enhance the effectiveness of rehabilitation plans and ensure a more complete functional independence and social reintegration of veterans.
Keywords: Occupational therapy; client-centered approach; functional independence; combat trauma; military personnel; occupation-based intervention; Canadian Occupational Performance Measure (COPM)